Pengaruh Total Assets Turnover, Cash Ratio Dan Working Net Capital terhadap Net Profit Margin pada Pt. Smartfren Telecom Tbk di Bursa Efek Indonesia Periode 2008-2017 - Ani Anggraini (Universitas Batanghari Jambi, 2019)
This study aims to analyze whether total assets turnover, cash ratio and working net capital have a significant or partial effect on the net profit margin at PT. Smartfren Telecom Tbk on the Indonesia Stock Exchange 2008-2017. This research uses quantitative descriptive analysis method and qualitative descriptive analysis. The analytical tool of this research is the same as the analytical method, namely multiple linear regression using log. The results of the study show that simultaneously from this study shows the effect of total assets turnover, cash ratio and net working capital on the net profit margin at PT. Smartfren Telecom Tbk which is listed on the Indonesia Stock Exchange for the period 2008-2017. Simultaneously with the number of Fcount 72,388 and Ftable 3.86, it can be seen that Fcount>Ftable is 72,398> 3.86, meaning that there is a significant effect on total assets turnover, cash ratio and net working capital on the net profit margin. Partial influence on total influence of assets turnover, cash ratio and net working capital ratio Against the net profit margin at PT. Smartfren Telecom Tbk, which is listed on the Indonesia Stock Exchange for the period 2008-2017 with the total assets turnover of t -10,466 and 2,570 tables means t count <table, -10,466 <2,570, meaning total assets turnover does not have a positive effect on net profit margin, cash ratio t count 1.556 and t table 2.570 means t count <t table, 1.556 <2.570, meaning that the cash ratio does not have a positive effect on the net profit margin and net working capital t count 0.368 and t table 2.570 is the meaning t count <t table, 0.368 <52,570 which means net working capital does not have a positive influence on the net profit margin for the period 2008-2017.